Gravity and strings - Ortín, Tomás, 1964- (Cambridge monographs on mathematical physics., 2004)
Gravity and Strings is a self-contained, pedagogical exposition of the theory of quantum gravity provided by string theory, presenting its foundations and its basic results. This book can be used as a reference book for researchers or as a complementary textbook in graduate courses on gravity, supergravity and string theory.